+0  
 
0
397
1
avatar+99 

The standard form of the equation of a circle is (x−3)2+(y−1)2=16.

 

What is the general form of the equation?

x2+y2−6x−2y−6=0

x2+y2+6x+2y+26=0

x2+y2−6x−2y−26=0

x2+y2+6x+2y−6=0

CrazyDaizy  Jun 6, 2017
edited by CrazyDaizy  Jun 6, 2017
 #1
avatar+7324 
+1

(x - 3)2 + (y - 1)2   =   16

 

To get this into general form, we need to multiply out   (x - 3)2   and   (y - 1)2 .

 

(x - 3)(x - 3)  +  (y - 1)(y - 1)   =   16                      First, let's just do (x - 3)2 .

 

x2 - 3x - 3x + 9  +  (y - 1)(y - 1)   =   16                Now, let's do (y - 1)2 .

 

x2 - 3x - 3x + 9  +  y2 - 1y - 1y + 1   =   16          Subtract 16 from both sides of the equation.

 

x2 - 3x - 3x + 9  +  y2 - 1y - 1y + 1 - 16   =   0     Combine like terms.

 

x2 - 6x + y2 - 2y - 6 = 0          Rearrange.

 

x2 + y2 - 6x - 2y - 6 = 0

hectictar  Jun 6, 2017

24 Online Users

avatar
avatar

New Privacy Policy

We use cookies to personalise content and advertisements and to analyse access to our website. Furthermore, our partners for online advertising receive information about your use of our website.
For more information: our cookie policy and privacy policy.